Old Engineering Hall, University of Washington, n.d. - Webster & Stevens
Engineering Hall built in 1908 as the Machinery Pavilion for the Alaska Yukon Pacific Exposition. Stamped on verso: Webster & Stevens print. Filed in: UW - Engineering Hall (Old) (#433).